Purification and Properties of UDP-GlcNAc:Dolichyl-Pyrophosphoryl-GlcNAc GlcNAc Transferase from Mung Bean Seedling - Kaushal, Gur P. (1986)
The N-acetylglucosamine (GlcNAc) transferase that catalyzes the formation of dolichyl-pyrophosphoryl-GlcNAc-GlcNAc from UDP-GlcNAc and dolichyl-pyrophosphoryl-GlcNAc was solubilized from the microsomal enzyme fraction of mung beans with 1.5% Triton X-100, and was purified 140-fold on columns of DE-52 and hydroxylapatite. The partially purified enzyme preparation was quite stable when stored in 20% glycerol and 0.5 millimolar dithiothreitol, and was free of GlcNAc-1-P transferase and mannosyl transferases. The GlcNAc transferase had a sharp pH optimum of 7.4 to 7.6 and the K(m) for dolichyl-pyrophosphoryl-GlcNAc was 2.2 micromolar and that for UDP-GlcNAc, 0.25 micromolar. The enzyme showed a strong requirement for the detergent Triton X-100 and was stimulated somewhat by the divalent cation Mg(2+). Uridine nucleotides, especially UDP and UDP-glucose inhibited the enzyme as did the antibiotic, diumycin. However, a variety of other antibiotics including tunicamycin were without effect. The product of the reaction was characterized as dolichyl-pyrophosphoryl-GlcNAc-GlcNAc.